2021
DOI: 10.1088/2053-1583/abe739
|View full text |Cite
|
Sign up to set email alerts
|

Direct growth of monolayer 1T–2H MoS2 heterostructures using KCl-assisted CVD process

Abstract: Accessing the metastable phases in a controlled fashion can further expand the applications of atomically thin transition metal dichalcogenides (TMDs). Although top-down approaches based on ion intercalation exfoliation have shown to be an effective route to transform 2H phase into 1T and/or 1T′ polytype phases, a bottom-up growth strategy could be more suitable for device integration. Herein, we show that by assisting the atmospheric pressure chemical vapor deposition (APCVD) growth with a specific alkali met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 43 publications
1
9
0
Order By: Relevance
“…Also, Raman analysis was done for monolayer MoS 2 as can be clearly seen in Figure 2b that the Raman spectroscopy had two distinct peaks centered at 384 cm −1 and 403 cm −1 , which corresponded to E 2g 1 and A 1g modes; where E 2g 1 signified in-plane vibration of M and S atoms and A 1g signified out-of-plane vibration and the frequency difference between in-plane and out-plane was observed to be 19 cm −1 confirming monolayer MoS 2 flakes. [31,32]…”
Section: Characterization Of Mosmentioning
confidence: 99%
“…Also, Raman analysis was done for monolayer MoS 2 as can be clearly seen in Figure 2b that the Raman spectroscopy had two distinct peaks centered at 384 cm −1 and 403 cm −1 , which corresponded to E 2g 1 and A 1g modes; where E 2g 1 signified in-plane vibration of M and S atoms and A 1g signified out-of-plane vibration and the frequency difference between in-plane and out-plane was observed to be 19 cm −1 confirming monolayer MoS 2 flakes. [31,32]…”
Section: Characterization Of Mosmentioning
confidence: 99%
“…Some approaches have been developed to obtain 1T-phase MoS 2 , such as chemical Li + intercalation/extraction exfoliation, , chemical vapor deposition (CVD), and solvothermal/hydrothermal method. , In spite of stunning developments in improving specific capacity of MoS 2 anodes, obvious capacity attenuation was accompanied for both cycling and rate performance. , It is ascribed to the habitual conversion of the metastable 1T-phase MoS 2 to the stable 2H phase via restacking in the charge–discharge process . In addition, the annealing process is usually required to improve the crystallinity of MoS 2 and form more active sites, but it also encounters the phase conversion from 1T to 2H. , Therefore, the formation of a stable 1T-phase MoS 2 that can withstand annealing and electrochemical cycling simultaneously is significant and challenging.…”
mentioning
confidence: 99%
“…Some approaches have been developed to obtain 1T-phase MoS 2 , such as chemical Li + intercalation/extraction exfoliation, 9,10 chemical vapor deposition (CVD), 11 and solvothermal/ hydrothermal method. 12,13 In spite of stunning developments in improving specific capacity of MoS 2 anodes, obvious capacity attenuation was accompanied for both cycling and rate performance.…”
mentioning
confidence: 99%
“…Although metal organic salts, such as perylene-3,4,9,10-tetracarboxylic acid tetrapotassium salts, were introduced in early CVD studies [9,25] remarkable improvements in growth have been demonstrated by the adoption of alkali metal halides (AMHs). [26][27][28][29][30][31][32][33][34][35][36][37][38] The versatility and practicality of AMH-assisted CVD are supported by the reduced process temperature, [26] millimeter-scaled large grains, [27] rapid growth, [27,28] and one-dimensional growth (TMD nanowire). [29] AMH-assisted CVD has evolved into a universal process capable of synthesizing more than 40 2D TMDs.…”
Section: Introductionmentioning
confidence: 99%